2011
DOI: 10.3945/jn.111.138651
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Does Not Inhibit the Absorption of 5 Milligrams of Nonheme or Heme Iron at Doses Less Than 800 Milligrams in Nonpregnant Women,

Abstract: Calcium is the only known component in the diet that may affect absorption of both nonheme and heme iron. However, the evidence for a calcium effect on iron absorption mainly comes from studies that did not isolate the effect of calcium from that of other dietary components, because it was detected in single-meal studies. Our objective was to establish potential effects of calcium on absorption of nonheme and heme iron and the dose response for this effect in the absence of a meal. Fifty-four healthy, nonpregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 24 publications
2
29
0
3
Order By: Relevance
“…In agreement with these results, a previous study performed by us, and recently published by Gaitan et al [15] found that doses ≤800 mg of Ca (CaCl 2 ) did not decrease the bioavailability of 5 mg of Fe (FeSO 4 ) in subjects with similar characteristics. Also, a study focused on the effect of calcium on uptake, efflux, and net absorption of non-heme iron using the intestinal-like epithelial Caco-2 cell found that calcium did not have an effect on the net absorption of non-heme iron [39].…”
Section: Subjectsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with these results, a previous study performed by us, and recently published by Gaitan et al [15] found that doses ≤800 mg of Ca (CaCl 2 ) did not decrease the bioavailability of 5 mg of Fe (FeSO 4 ) in subjects with similar characteristics. Also, a study focused on the effect of calcium on uptake, efflux, and net absorption of non-heme iron using the intestinal-like epithelial Caco-2 cell found that calcium did not have an effect on the net absorption of non-heme iron [39].…”
Section: Subjectsupporting
confidence: 92%
“…One study showed an inhibitory effect of phytic acid on iron absorption in the presence of calcium [14]. Although it has been thought that calcium may have a direct inhibitory effect on iron absorption, a recent article [15] showed that doses ≤800 mg of calcium (Ca molar ratio: Fe ≤ 225:1), do not diminish the bioavailability of 5 mg of non-heme iron. Evidence on the interaction between calcium and phytic acid and their effect http://dx.doi.org/10.1016/j.jtemb.2014.…”
Section: Introductionmentioning
confidence: 97%
“…The authors suggested that the reason for the adverse effect may be that physiological changes at the femoral neck are inhibited when high calcium supplementation is taken without vitamin D. An alternative explanation could be a reduced uptake of other potentially bone-essential minerals such as iron with high calcium intake [44,45]. But this inhibitory effect seems to be of short term duration and only present at very high calcium doses [45][46][47].…”
Section: Discussionmentioning
confidence: 92%
“…In the human study, the calcium dose selected was 600 mg, because this quantity of calcium was required to achieve a calcium:iron molar ratio of 11∶1 with the minimum dose of iron required to produce a measurable serum response (21 mg). A dose-dependent inhibitory effect of calcium on absorption of iron has been reported for molar ratios ranging from 11∶1 (40 mg calcium, 5 mg iron) to 83∶1 (300 mg calcium, 5 mg iron) [25], although more recently a higher threshold molar ratio of 220∶1 (800 mg calcium, 5 mg iron) was reported [26]. Our study demonstrates an inhibitory effect of calcium at a molar ratio of 11∶1 (Figure 3, iron alone 11.5%, iron plus calcium 5.6%, p = 0.014, n = 7).…”
Section: Discussionmentioning
confidence: 99%